Analysis Of Interest Preferences In Using the Agen46 - Yuniartha, I Putu Ngurah Bagus; Darma, Gede Sri (International Journal of Economics Development Research (IJEDR), 2024)
This study used a total of 115 respondents from customers who use Agen46 BNI who transact in the Bali and Nusa Tenggara regions. The goal is to find out the factors related to satisfaction with the use of the application. Hypothesis testing uses SEM (Structural Equation Modeling) analysis tools. The results found that the perception of application use has a positive and significant influence on belief and satisfaction, as well as the benefit factor on belief and satisfaction. In addition, belief has a positive and significant influence on satisfaction. Similarly, satisfaction with the interest in using also had a positive and significant relationship. But for mediating relationships, belief is not able to significantly mediate the relationship between use and satisfaction. The same results also apply to the relationship of belief mediation between benefits and satisfaction.